The organizational design for the OASIS Business Group Ltda. Of the municipality of Puerto Gaitán by Ángela Rey - Kent Hurtado (GEON Journal (Management, Organizations and Business), 2015)
Companies are challenged to survive in a changing environment today where only those who manage to overcome the challenges that arise day to day manage to stay on the market. The Oasis Ltda., Business Group is a micro of Meta who wants to improve their administrative processes and their market position, the company structurally organizing and standardizing their production processes. The project was carried out with the aim of proposing an administrative and organizational structure for the company processes Oasis Grupo Empresarial Ltda., For the purpose of establishing an organizational model in line with the business strategy that has been developing its business in a few years creation. This proposal was developed by designing an organizational structure by processes according to the nature of business, the development of a manual of functions in order to have clarity in the description and functions of the job, and design manuals procedures to standardize and improve their production processes.
Keywords: Strategic Management; Process; Vision; Mission